Reflections about Inclusive Education in Colombia: State of topic - Reina Avila, Katherine Gabriela; Lara Buitrago, Paola Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article is a documentary review of academic articles published in specialized journals, related to inclusive education and the teaching of English in Colombia, in a period of time between 2006 and 2019. A rigorous content analysis was carried out with instruments of information gathering such as: thematic files and categorical matrices. The results were grouped into the following categories: concept of inclusive education; legislation and regulations; experiences in educational contexts; studies on inclusive education and ways of teaching. It is concluded that, despite the efforts made by the Colombian government, educational institutions, teachers and researchers, more research is still required on the teaching of English to inclusion students to guarantee quality education to this student population.